Chikungunya on the move- reflection from Pakistan - Bukhari, Syeda Rohma; Mahmood, Syed Uzair; Jamal, Ayesha Marium; Syed, Maryam Jamil; Bukhari, Syeda Ifrah (International Journal Of Community Medicine And Public Health, 2018)
Chikungungya is not a recently discovered disease but it came into lime light again when three of the seven continents suffered a recent outbreak. The disease, its virus and the vector- the Aedes aegypti mosquito, were first described by Marion Robinson and William Hepburn Russell Lumsden in 1955. Out of fever, maculo-papular rash and joint paint; severe arthralgia dominates the symptoms of chikungunya, and that is why the word itself, translated into the language of is origin i.e. Makonde, means to become distorted. Many research studies have been conducted to find a vaccine. Lack of awareness in Pakistan and misdiagnosis has led consequently to an alarming number of cases over all in Pakistan but especially the Malir district of Karachi. Efforts to take pre cautions by increasing awareness about the disease and preventive measures such as eliminating breeding sites and avoiding mosquito bites can easily contain spread of disease.